Commercial Pressures on Professionalism in American Medical Care: From Medicare to the Affordable Care Act. Issue 4 (2014) - Marmor, Theodore R.; Gordon, Robert W.
Abstract : This essay describes how longstanding conceptions of professionalism in American medical care came under attack in the decades since the enactment of Medicare in 1965 and how the reform strategy and core provisions of the 2010 Affordable Care Act (ACA) illustrate the weakening of those ideas and the institutional practices embodying them. The opening identifies the dominant role of physicians in American medical care in the two decades after World War II. By the time Medicare was enacted in 1965, associations of American physicians were almost completely in charge of medical education, specialist certification, and the enforcement of professional norms on their members. Who could be a doctor, what education and training would be required, and what collegial oversight was operative was first a professional matter and only secondly implicated the state through malpractice or major corporations via the employment of physicians.